Individual and organizational support: Does it affect red tape, stress and work outcomes of police officers in the USA?. Issue 4 (5th June 2017) - Brunetto, Yvonne; Teo, Stephen T.T.; Farr-Wharton, Rodney; Shacklock, Kate; Shriberg, Art
Abstract : Purpose: The purpose of this paper is to examine whether management supports police officers adequately, or whether police have to rely on their individual attributes, specifically psychological capital (PsyCap), to cope with red tape and stress. Work outcomes/consequences examined were discretionary power, affective commitment and turnover intentions. Design/methodology/approach: A cross-sectional design using a survey-based, self-report strategy was used to collect data from 588 police officers from USA, who are most engaged with the public. The data were analysed using AMOS and a structural model to undertake structural equation modelling. Findings: Two significant paths were identified Path 1: management support to red tape to discretionary power to affective commitment and turnover intentions; and Path 2: supervisor relationships to PsyCap to stress to affective commitment and turnover intentions. Further, management support predicted PsyCap, red tape and police stressors. Red tape increased police stressors and turnover intentions. Research limitations/implications: The use of self-report surveys is a limitation, causing common methods bias. Using Harmon's one-factor post hoc test, the authors were able to provide some assurance that common method bias was of no major concern. Originality/value: As far as is known, this study is the first to examine, for police officers, how PsyCap impacts upon negative factors (stress and red tape) and enhances positive drivers for employees. Examining the impact of an individual attribute – PsyCap – provides an important piece of the organizational puzzle in explaining the commitment and turnover intentions of police officers. By examining the impact of both organizational and individual factors, there is now more knowledge about the antecedents of police outcomes.